2007
DOI: 10.1016/j.ejcts.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ascending aortic dilatation with bicuspid aortic valve: a wide spectrum of disease expression☆

Abstract: BAV patients constitute an importantly heterogeneous population in terms of risk and features of aortic disease. The most common condition is an ectasia of the mid-ascending tract, with unaffected or mildly involved root. If further confirmed, this could suggest that surgical approach may spare the root in most BAV patients. Mid-ascending dilatation is proportional to stenosis severity, suggesting a post-stenotic causative mechanism. Root dilatation is rarer, mostly observed in younger men, and unrelated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
239
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(260 citation statements)
references
References 25 publications
14
239
3
4
Order By: Relevance
“…Dilatation of the aortic root is described to be relatively rare in BAV and is proposed to be the form of bicuspid aortopathy most likely to be associated with a genetic cause. 3,13,20,24,[31][32][33] The other studies reported percentages of TAA in the first-degree TAV relatives of 3-4%. 54,[65][66][67][68] This is around population risk since 2.3% of the general population, by definition, is expected to have z scores >2.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dilatation of the aortic root is described to be relatively rare in BAV and is proposed to be the form of bicuspid aortopathy most likely to be associated with a genetic cause. 3,13,20,24,[31][32][33] The other studies reported percentages of TAA in the first-degree TAV relatives of 3-4%. 54,[65][66][67][68] This is around population risk since 2.3% of the general population, by definition, is expected to have z scores >2.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectsmentioning
confidence: 99%
“…This root phenotype has been proposed to be the form of bicuspid aortopathy most likely to be associated with a genetic cause. 3,13,20,24,[31][32][33] Although rare, the most feared complication in BAV patients is thoracic aortic dissection, which has been reported at young age. 34 Whereas the lifetime risk of aortic dissection in BAV patients was initially reported around 5%, recent studies show a lifetime risk of aortic dissection of less than 1% in BAV patients and a normal life expectancy.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The association between BAV stenosis and asymmetric mid-ascending aortic dilatation has been proposed to be pathogenetic (Della Corte et al, 2007). It has been proved that stenosis of the BAV, which is geometrically asymmetrical, produces an eccentric turbulent transvalvular blood flow that results in asymmetrical wall stress distribution in the ascending aorta ( Fig.…”
Section: Bav Stenosis With An Asymmetric Mid-ascending Aortic Dilatationmentioning
confidence: 99%
“…Several factors are associated with progressive aortic dilatation and include age, hypertension, male gender, aortic valve disease, and valve morphologies. 8,16,17 Evaluation of the aortic dimensions in BAV patients is mandatory. In a prospective community study from Olmsted County, Minnesota, USA, aortic aneurysm (an ascending aorta ≥45 mm) was identified in 7.7% of BAV patients at baseline with a mean age of 55 years.…”
Section: Bav and Aortopathymentioning
confidence: 99%